PERANCANGAN SISTEM PACKING BERAS OTOMATIS MENGGUNAKAN ARDUINO UNO - RIZKY M ALFI; AGUS SUGIHARTO; MUNNIK HARYANTI; BEKTI YULIANTI (JURNAL TEKNIK INDUSTRI, 2021)
ABSTRAKAt this time, we need a tool to process the product arrangement, and packing or packing. The packaging functions so that the item is not easily damaged, due to external factors. As from the weather and pests when it will be saved. The rice filling packing device is designed quite simple, which can automatically control the packaging system design or the goods packing system using a conveyor, which is driven through a microcontroller. From this measurement tool can work quite well in terms of the packing process with the measurement media with the distance between the infrared sensor that detects the packaging. Keyword : Packing, Filling Rice, Microcontroller, Infra Red